Chemical composition and enzyme inhibition of Phytolacca dioica L. seeds extracts. (1st January 2019) - Di Petrillo, Amalia; María González-Paramás, Ana; Rosa, Antonella; Ruggiero, Valeria; Boylan, Fabio; Kumar, Amit; Pintus, Francesca; Santos-Buelga, Celestino; Fais, Antonella; Era, Benedetta
Abstract: Phytolacca, which belongs to the family of Phytolaccaceae, are known for their use in popular medicine. Bioactivity of five extracts from Phytolacca dioica seeds were evaluated in four bioassays. A selected group of compounds from the extract that displayed the best bioactivity was analysed. The ethyl acetate extract (EAE) possessed the highest content of phenolics, the highest inhibitory activity on the tyrosinase and xanthine oxidase enzymes and showed a high antioxidant activity. HPLC-DAD-MS was employed to identify the phenolics profile of the most active one (EAE). HSCCC analysis of the EAE led to the isolation of phytolaccoside B and a mixture of 4 isomers, isoamericanol B1, B2, C1 and C2. These isoamericanol isomers presented activity against tyrosinase and xanthine oxidase. Our results revealed for the first time an interesting biological activity of the extract and isolated compounds from P. dioica seeds, which could be considered as a source of bioactive molecules.